The Influence of Conflict Management, Employee Engagement, and Work-Life Balance on Productivity through Well-Being - Saragih, Junawi Hartasi; Siahaan, Elisabet; Gultom, Parapat (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study analyzes the influence of conflict management, employee engagement, and work-life balance on employee productivity at BPS North Sumatra with employee well-being as a mediating variable. Using a quantitative approach, this study involved 111 BPS Sumatera Utara Province employees through total sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that conflict management, employee engagement, and work-life balance positively and significantly influence employee productivity, both directly and through the mediation of employee well-being. Employee well-being effectively mediates the influence of all three independent variables on employee productivity. This study provides recommendations for improving employee productivity through effective conflict management, enhanced employee engagement, and optimization of work-life balance.